Comparison of Intranasal Dexmedetomidine and Oral Midazolam for Premedication in Pediatric Dental Patients under General Anesthesia: A Randomised Clinical Trial - Wang, Li (Biomed Res Int, 2020)
The aim of this study was to compare the effects of preoperative intranasal dexmedetomidine and oral midazolam on preoperative sedation and postoperative agitation in pediatric dentistry. A total of 60 children (ASA grade I, aged 3–6 years) scheduled for elective pediatric dental treatment were randomly divided into the dexmedetomidine (DEX) and midazolam (MID) groups. Ramsay sedation score, parental separation anxiety scale, mask acceptance scale, pediatric anesthesia emergence delirium scale, and hemodynamic parameters were recorded. The Ramsay sedation scale and hemodynamic parameters of the children were observed and recorded immediately before administration and 10, 20, and 30 min after administration. A satisfactory mask acceptance scale rate was 93.33% in both MID and DEX groups, and there was no significant difference between the two groups (p > 0.05). The proportions of children that “successfully separated from their parents” were 93.33% (MID) and 96.67% (DEX). No significant difference was found between the two groups (p > 0.05). The incidence of agitation was 20% in the MID group and 0% in the DEX group, and the difference was statistically significant (p < 0.05). Intranasal dexmedetomidine and oral midazolam provided satisfactory sedation. No significant difference between the two groups was found in terms of parental separation anxiety and mask acceptance (p > 0.05). The incidence of postoperative pediatrics emergence delirium was significantly lower in the DEX group (p < 0.05).